Possibility on Agriculture Mechanization for Tropical Yam ( Dioscorea Hispida) - Haji Razali, Mohd Hudzari; Mohd Noor, Noordin Asimi; Wan Musa, Wan Muzawati; M.A.H.A, Ssomad (2012)
Ubi Gadong (Dioscorea hispida) is a toxic plant which contains toxic poison. It can only be consumed after the poison of dioscorin is removed. It is normafly found in wildlife forest and planted in clay soil condition in Asia region. The advancement of technology should introduce in most important area; agriculture, as for benefit of mankind. The solid modeling software may use for design, model and simulate the workability of the designed equipment in CAD environment system. The simulation analysis will make the designer choose the best decision for fabrication stage of agriculture mechanization tool. The farm mechanization for ubi gadong is help to produce the good quality and output in this new exploration of wildlife food for commercialization.